A new solution to a weakly non-linear heat conduction equation in a spherical droplet: Basic idea and applications - Antonov D. V. Dmitry Vladimirovich; Shchepakina E. A. Elena Anatoljevna; Sobolev V. A. Vladimir Aleksandrovich; Starinskaya E. M. Elena Mikhaylovna; Terekhov V. V. Vladimir Vladimirovich; Strizhak P. A. Pavel Alexandrovich; Sazhin S. S. Sergey Stepanovich (2024, 2024)
Title screen